Preparation of future teachers of mathematics for effective implementation of computer educational programs in general secondary education institutions - Chernova, Ganna (Scientific notes of the pedagogical department, 2023)
The modern education system in the conditions of reform needs professional mathematics teachers, competitive, able to think creatively, experiment, introduce innovations in their pedagogical activity, and form a full-fledged intellectual personality of the student. In this aspect, the training of mathematics teachers who are able to effectively introduce computer educational programs into the educational process of students becomes relevant.The purpose of the article is to generalize the definition of a teacher’s digital competence, to identify the main computer educational programs that future mathematics teachers can effectively use in their pedagogical activities with students, to provide a recommendation on the training of mathematics teachers, aimed at the effective use of electronic educational services in institutions of general secondary education.Based on the analysis of scientific literature, it was found that the level of formation of the teacher’s digital competence affects the quality of the educational process. At the same time, it was found that digital competence is a combination of general and special knowledge, abilities, and skills of a teacher to achieve educational goals through the effective use of computer technologies in the educational process.Three basic component structures of digital competence are distinguished: general, didactic, and professionally oriented (social).A list of popular computer educational services, convenient for use in mathematics lessons, is provided, and their main educational capabilities are presented.Recommendations on the effective use of computer educational programs by students in the educational and educational activities of students are offered.Using the example of the existing educational program, it is outlined how the effective introduction of computer educational services in the training of mathematics teachers takes place.Based on the conducted research, it was concluded that the preparation of future mathematics teachers for the effective use of computer resources in the education of students should be carried out taking into account the following conditions: the presence of a clear motivation to use computer educational services; deep understanding of the educational possibilities of using digital technologies; expediency and dosage of using relevant services; willingness of educators to continuously improve themselves in professional pedagogical activity.Prospects for further scientific research are outlined.